2002
DOI: 10.1073/pnas.162006499
|View full text |Cite
|
Sign up to set email alerts
|

MHC heterozygosity confers a selective advantage against multiple-strain infections

Abstract: Genetic heterozygosity is thought to enhance resistance of hosts to infectious diseases, but few tests of this idea exist. In particular, heterozygosity at the MHC, the highly polymorphic loci that control immunological recognition of pathogens, is suspected to confer a selective advantage by enhancing resistance to infectious diseases (the ''heterozygote advantage'' hypothesis). To test this hypothesis, we released mice into large population enclosures and challenged them with multiple strains of Salmonella a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
478
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(491 citation statements)
references
References 52 publications
12
478
1
Order By: Relevance
“…(c) MHC and fitness Increased MHC diversity has been both theoretically and empirically linked to increased pathogen resistance and survival (Potts & Slev 1995;Hedrick 2002;Penn et al 2002). Indeed, strong pathogen-mediated balancing selection is thought to be responsible for maintaining the remarkably high levels of variation observed at several MHC loci in the otherwise genetically monomorphic endemic San Nicolas Island fox, Urocyon littoralis dickeyi (Aguilar et al 2004).…”
Section: Discussion (A) Mhc-based Mate Choicementioning
confidence: 99%
“…(c) MHC and fitness Increased MHC diversity has been both theoretically and empirically linked to increased pathogen resistance and survival (Potts & Slev 1995;Hedrick 2002;Penn et al 2002). Indeed, strong pathogen-mediated balancing selection is thought to be responsible for maintaining the remarkably high levels of variation observed at several MHC loci in the otherwise genetically monomorphic endemic San Nicolas Island fox, Urocyon littoralis dickeyi (Aguilar et al 2004).…”
Section: Discussion (A) Mhc-based Mate Choicementioning
confidence: 99%
“…MHC heterozygosity has been shown to be associated with decreased infection rates in both laboratory and field studies (McClelland et al 2003;Froeschke and Sommer 2005), but several other studies have found no such association (Harf and Sommer 2005;Dionne et al 2009). Ilmonen et al (2007) found that wild-derived mice that were MHC heterozygotes did not show better resistance to Salmonella or better survival in semi-natural enclosures, even though earlier laboratory experiments documented a heterozygote advantage (Penn et al 2002). These results emphasise the importance of studies on wild, outbred species.…”
Section: Effects Of the Mhc On Infection And Survival Ratesmentioning
confidence: 95%
“…A commonly held view is that the polymorphism is due to selection favoring MHC heterozygous hosts (Doherty and Zinkernagel 1975;Nei 1988, 1989;Takahata and Nei 1990;Hughes and Nei 1992). Since different MHC molecules bind different peptides, MHC heterozygous hosts can present a greater variety of peptides, and hence defend themselves against a larger variety of pathogens compared with MHC homozygous individuals (Penn et al 2002). It has indeed been shown that MHC heterozygosity correlates negatively with disease in HIV-infected patients (Carrington et al 1999), with HTLV-1 infection in humans (Jeffery et al 2000), and with LCMV infection in mice (Weidt et al 1995).…”
Section: Introductionmentioning
confidence: 99%